Short anagen syndrome of the hairline. - Milano, A. (European Journal of Pediatric Dermatology, 2020)
The anagen phase, during which the hair grows and lengthens by about 0.3 mm per day, lasts 2-6 years. The duration of the anagen phase is influenced by several factors, including the location; the eyebrows have shorter hairs because the anagen phase in this area is shorter. In the literature (1, 2) there are about twenty cases of short anagen syndrome, which prevails in the female sex and in subjects with blond hair; it is usually sporadic but sometimes familial. One thinks of this syndrome when one hears that the hair has never been cut. The clinical suspicion is confirmed by the presence of hair mainly in the telogen phase and pencil tip-shaped under microscopic examination. How-ever, all hair is usually affected and not only in the hairline: to explain the location of our case we assume a particular predisposition of the hairline to be affected by the factors that determine the short anagen syndrome.